Comparing the effectiveness of landslide susceptibility mapping by using the frequency ratio and hybrid MCDM models - Jonmenjoy Barman; Syed Sadath Ali; Teachersunday Nongrem; Brototi Biswas; K. Srinivasa Rao; Malay Pramanik; Fahdah Falah Ben Hasher; Mohamed Zhran (Results in Engineering)
The present study involved the landslide susceptibility mapping of Indian state of Meghalaya by using the frequency ratio (FR) and Analytical Hierarchy Process (AHP)- VlseKriterijuska Optimizacija I Komoromisno Resenje (VIKOR) (AHP-VIKOR), and the outcomes were validated and compared. Therefore, fourteen landslide conditioning factors were selected after a multi-collinearity test by tolerance and variance Inflation Factor. Based on 70 % of the training data, the relative frequency and predictive rate value was used to generate final output. In opposite, the overall ranking was used to generate landslide susceptibility map (LSM) for the AHP-VIKOR model. Subsequently, the generated LSM was classified into five hierarchical zones from very low to very high based on the natural breaking classification. The area under the curve of receiver operating characteristics from 30 % of validation landslides shown more predictive accuracy of AHP-VIKOR model than FR model under similar geo-environmental condition. The spatial distribution of landslide susceptibility zones shows that 37 % of the region under the threat of having a high landslip risk. Landslides are primarily found in barren Cretaceous sedimentary rocks, with increased risk near roadsides. This is due to slope cutting for roads, making hilly terrain unstable. Areas with more annual rainfall face greater landslide threats. Therefore, the outcome of the study may contain the useful information that helps the local administration to recognize vulnerability of landslides as well as to take up the hazard mitigative measures.